Navigating Between Environmental and Social Sustainability: Different Paths of EU Electricity Production Transformation and Their Impact on Household Consumers Electricity Prices - Ošlovnik, Tinkara; Denac, Matjaž (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The phase-out of asbestos in urban environments represents a complex challenge across European municipalities. Despite European Union targets to achieve asbestos-free cities, implementation remains uneven because municipalities face fragmented regulations, differing inspection and disclosure requirements, limited funding, technical constraints, and variable public awareness. The paper identifies key barriers, including regulatory heterogeneity, inadequate disposal infrastructure, financing gaps, and institutional coordination challenges, alongside enabling factors such as harmonized policies, innovative treatment technologies, capacity-building programs, community engagement, and transparent governance. Based on these insights, a typology of municipal transition pathways is developed, including compliance-driven, retrofit-integrated, innovation-led, community-driven, and market-based approaches. The findings underline equity considerations, emphasizing the need to prevent disadvantaged communities from remaining disproportionately exposed to asbestos hazards. By framing asbestos removal as a material legacy transition within broader urban sustainability transitions, the paper contributes to theoretical understanding of socio-technical and ecosystem dynamics while offering practical guidance for policymakers, urban planners, and other stakeholders seeking resilient, equitable, and sustainable asbestos-free municipalities across Europe. It also highlights the importance of integrated governance, long-term financing, systematic monitoring, knowledge sharing between municipalities, stakeholder collaboration, regulatory consistency, public communication, workforce training, and continuous policy learning to accelerate safe, effective, scalable implementation across diverse European regions sustainably.